Green Infrastructure as a Factor for Sustainable Development of Khabarovsk - Galina Yuryevna Morozova; Irina Dmitrievna Debelaya (Экономика региона, 2018)
Green infrastructure is considered as a factor for the sustainable development of a city. The indicators of urban greening as well as the state and resistance of plantings to the urban environment are the indicators of the sustainable development of the cities and towns. Greening is the basis for green infrastructure, because it develops ecologically safe, esthetically attractive and comfortable urban environment. The purpose of the article is to assess the role of greening Khabarovsk as the main component of green infrastructure. We have used the method of forest estimation, the population and statistical methods. To assess the effectiveness of the municipal programme for the enhancement of the urban environment, we have analyzed the “cost-benefit” on the example of a city park. The territorial planning was based on the priority of economic development, and financing was insufficient. These facts lead to the problems in the protection and reproduction of green plantings of Khabarovsk. The strengthening of economic development caused the deterioration of the ecological status of the territory. The assessment of the current urban plantation has revealed a constant decrease of urban greening, a high percent of old-age plantings as well as a decrease in plant life because of urban stress. Extending the range and lands for greening during urban renovation is a positive trend. Green spaces except for socio-economic infrastructure are the major ecosystem services. The methods for their assessment are still in the early stage of development. The preliminary assessment of ecosystem functions using the “cost-benefit” method on the example of the city park has allowed increasing the economic value of the green space, drawing attention to the reduction of the area for greening as well as to the need for maintaining the high viability of plants. The cities are priority territories to develop a system of payments for ecosystem services, which provide sustainable development of a region. The results can be applied in the ecological planning of urban space, regional environmental policy, and municipal management. The green infrastructure is a multipurpose infrastructure, which improves ecological situation in Khabarovsk, creates favorable conditions for both the citizens and investment climate as well as promotes domestic and inbound tourism.